Measurements of the pp → W±γγ and pp → Zγγ cross sections at √s = 13 TeV and limits on anomalous quartic gauge couplings; Journal of High Energy Physics; Vol. 2021, iss. 10 - Tumasyan A. R.; Adam W. Wolfgang; Andrejkovic J. W. Aleksandr Dmitrievich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen